Effect of alloying and aging on morphological changes from lamellar to equiaxed microstructure of α2 + γ titanium aluminides - Sreenivasulu G.; Singh A.K.; Mukhopadhyay N.K.; Sastry G.V.S. (My University, 2025)
The stability of a lamellar structure consisting of α2 and γ phases in alloys Ti-48Al, Ti-48Al-2Mo, Ti-48Al-4Nb, and Ti-48Al-1Mo-4Nb has been studied as a function of aging time and temperature. The alloys were solution treated (1400 °C, 30 min, and air-cooled (AC)) and aged at 1000 °C and 1100 °C for 1, 4, and 16 hours, respectively. The results indicate that the kinetics of lamellae to equiaxed transformation depends on alloy chemistry, aging time, and temperature. The Nb decreases and Mo increases the kinetics of transformation. The combined effect of Nb and Mo results in the highest volume fraction of equiaxed microstructure at a given aging time and temperature. The results have been discussed in relation to microstructural features and have been compared with those reported in other α2 + γ alloys.